2009
DOI: 10.1111/j.1365-2710.2009.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in folate pathway enzymes as a possible marker for predicting the outcome of methotrexate therapy in Japanese patients with rheumatoid arthritis

Abstract: Patients with RA having RFC 80A and GGH-401T alleles were less responsive to MTX than those with RFC 80A and without GGH-401T alleles. Thus, this data may be useful for guiding treatment of RA patients with MTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 34 publications
2
25
0
4
Order By: Relevance
“…Supporting this observation studies in RA patients have found correlation between GGH 401T allele with reduced efficacy [34] and lower MTXPG accumulation [24]. We observed GGH 401TT was associated with hepatic and overall AE in our RA patients.…”
Section: Effect Of Snps In Folate Metabolism On Mtx Response Researchsupporting
confidence: 77%
“…Supporting this observation studies in RA patients have found correlation between GGH 401T allele with reduced efficacy [34] and lower MTXPG accumulation [24]. We observed GGH 401TT was associated with hepatic and overall AE in our RA patients.…”
Section: Effect Of Snps In Folate Metabolism On Mtx Response Researchsupporting
confidence: 77%
“…High GGH expression was shown to be associated with a higher risk of developing advanced toxicity to pemetrexed, a multi-targeted antifolate, in patients with advanced breast cancer (Llombart-Cussac et al 2007). Furthermore, several recently identified and characterized functionally significant genetic and epigenetic polymorphisms of GGH have been reported to predict response to and toxicity of antifolate-based treatment in patients with several cancers (Cheng et al 2004;Kim et al 2008;Koomdee et al 2012;Silva et al 2013;Smit et al 2012;Wang et al 2014) and inflammatory arthritis (Dervieux et al 2004;Hayashi et al 2009;Jekic et al 2013;Owen et al 2012;van der Straaten et al 2007;Yanagimachi et al 2011). Our data herein provide evidence that GGH modulation significantly influences expression and CpG DNA methylation of genes involved in important biological pathways that might account for the observed effects of GGH modulation on cancer risk, prognosis, and treatment response.…”
Section: Discussionsupporting
confidence: 54%
“…Data from 27 studies investigating MTHFR SNPs and MTX related efficacy and toxicity in RA patients were initially identified through the database searches [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][45][46][47][48][49][50][51][52][53][54] and combined with results from our study, leaving 28 studies for review. From these, 11 studies were excluded due to lack of available data, leaving 17 studies including the present study published between 2001 and 2010 meeting the eligibility criteria, which were included in the meta-analysis: [18][19][20][22][23][24][25][26][27][28]32,33,45,46,53,54 For the C677T SNP, 10 studies were included for the efficacy analysis and 13 studies for the toxicity analysis (Table 2) and for the A1298C SNP 8 studies were included for the efficacy analysis and 8 studies for the toxicity analysis (Table 3).…”
Section: Meta-analysis: Studies Includedmentioning
confidence: 99%